Journeying - Magris, Claudio (Margellos world republic of letters book., 2018)
A writer for whom the journey has always mattered reinvents the very form itself in this inviting collection of in-the-moment impressions of his journeys A writer of enormous erudition and wide-ranging travels, Claudio Magris selects for this volume writings penned during trips and wanderings over the span of several decades. He has traveled through these years with many beloved companions, to whom he dedicates the book, and sought the kind of journey "that occurs when you abandon yourself to [the gentle current of time] and to whatever life brings." Taken together Magris's essays share a clearly identified theme. They represent the motif of the journey in all its aspects--literary, metaphysical, spiritual, mythical, philosophical, historical--as well as the author's comprehensive understanding of the subject or, one might say, of his own way of being in the world. Traveling from Spain to Germany to Poland, Norway, Vietnam, Iran, and Australia, he records particular moments and places through a highly personal lens. A writer's writer and a reader's traveler, Magris proves that wandering is equal part wondering.